Canine bartonellosis: serological and molecular prevalence in Brazil and evidence of co-infection with Bartonella henselae and Bartonella vinsonii subsp berkhoffii - Vissotto de Paiva Diniz, Pedro Paulo; Maggi, Ricardo Guillermo; Schwartz, Denise Saretta; Cadenas, Maria Belen; Bradley, Julie Meredith; Hegarty, Barbara; Breitschwerdt, Edward Bealmear (Edp Sciences S A, 2007)
The purpose of this study was to determine the serological and molecular prevalence of Bartonella spp. infection in a sick dog population from Brazil. At the São Paulo State University Veterinary Teaching Hospital in Botucatu, 198 consecutive dogs with clinicopathological abnormalities consistent with tick-borne infections were sampled. Antibodies to Bartonella henselae and Bartonella vinsonii subsp. berkhoffii were detected in 2.0% ( 4/197) and 1.5% ( 3/197) of the dogs, respectively. Using 16S-23S rRNA intergenic transcribed spacer ( ITS) primers, Bartonella DNA was amplified from only 1/198 blood samples. Bartonella seroreactive and/or PCR positive blood samples ( n = 8) were inoculated into a liquid pre-enrichment growth medium ( BAPGM) and subsequently sub-inoculated onto BAPGM/blood-agar plates. PCR targeting the ITS region, pap31 and rpoB genes amplified B. henselae from the blood and/or isolates of the PCR positive dog ( ITS: DQ346666; pap31 gene: DQ351240; rpoB: EF196806). B. henselae and B. vinsonii subsp. berkhoffii ( pap31: DQ906160; rpoB: EF196805) co-infection was found in one of the B. vinsonii subsp. berkhoffii seroreactive dogs. We conclude that dogs in this study population were infrequently exposed to or infected with a Bartonella species. The B. henselae and B. vinsonii subsp. berkhoffii strains identified in this study are genetically similar to strains isolated from septicemic cats, dogs, coyotes and human beings from other parts of the world. To our knowledge, these isolates provide the first Brazilian DNA sequences from these Bartonella species and the first evidence of Bartonella co-infection in dogs.
Keywords: dogs; Bartonella infections; heart disease; culture; Brazil